Technological Innovation in the Implementation of Traffic Dikmas in the Jurisdiction of the Bandung Polrestabes - Reswara, Gusti Adhira (Police Studies Review, 2024)
This research is motivated by the need for technological innovation to support the optimization of the Dikmas Lantas in order to tackle the problem of traffic violations and accidents. Therefore this research is aimed at explaining the implementation of the Dikmas Lantas, the factors that influence the implementation of the Dikmas Lantas and technological innovations in the implementation of the Dikmas Lantas in the jurisdiction of Polrestabes Bandung. Theories used in this study include management theory, the concept of technological innovation, and the concept of public education about traffic. This research was conducted with field research methods presented with a qualitative approach and analyzed with data triangulation techniques. The results of this study indicate that Dikmas Lantas has been carried out so far using conventional methods and has the disadvantage of not being able to reach all levels of society that are targeted in the city of Bandung and not in accordance with the demands of the current development. The inhibiting factors for the implementation of the Dikmas Lantas came from the limited number of personnel, while the supporting factors came from the availability of facilities, infrastructure, and the existence of good community responses. Technological innovations in the implementation of the Dikmas Lantas learning method in the form of the Dikmas Lantas learning method are displayed virtually and integrated with the Bandung Command Center system on several social media connected to the system, such as: twetter, facebook, and youtube. The suggestion of this research is to maximize technological innovations in the implementation of the Dikmas Lantas, it requires good coordination between the National Police and the Bandung City Government and the society to jointly utilize the Dikmas Lantas learning media optimally so that the objectives of the Dikmas Lantas implementation are achieved.